Whole-genome probe capture sequencing reveals genomic diversity and characteristics of Mycoplasma pneumoniae in Nanjing, China - Zhou, Guilan; Yu, Yan; Ge, Teng; Tang, Chenyu; Zhang, Hongbo; He, Min (Frontiers in Microbiology, 2025)
Mycoplasma pneumoniae (M. pneumoniae), a slow-growing, fastidious Gram-negative bacterium and a leading cause of community-acquired pneumonia globally, remains understudied and underreported across numerous geographical areas in China despite its worldwide significance. This study employed probe capture sequencing for targeted enrichment and direct sequencing of M. pneumoniae from clinical samples, combined with comparative genomic analyses of contemporary and historical global genomes. Core genome and pan-genome revealed that the M. pneumoniae genomes were classified into two distinct clades, P1-I and P1-II, each associated with a specific sequence type (ST). Most of the genomes sequenced in this study were identified as P1-I (86.96%, 20/23), contrasting with the previously reported predominance of P1-II in the area. A limited number of single-nucleotide variations were identified in the virulence-associated genes between P1-I and P1-II, leading to amino acid substitutions. The A2063G point mutation in the 23S rRNA gene was detected in all sequenced genomes (23/23), demonstrating a 100% mutation rate. This study provides the first reported application of probe capture methodology for M. pneumoniae, highlighting the critical importance of sustained surveillance efforts to monitor the evolution and epidemiology of this pathogen.